Management of Dental Trauma in Children - Farwa Ghulam, Zainab Naushad, Sufyan Ahmed, Hijab Fatemah, Asad Farooq, Yousuf Moosa (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The Objective of this study was to survey the management procedures for dental trauma in children. The research analyzed the predominance of various sorts of dental trauma, the quick and long haul the executives rehearses, and the results of these mediations in a clinical setting. Methodology: A cross-sectional research design was utilized in this research. The sample included 200 children matured 6 to 12 years, chose utilizing purposive sampling. Data were assembled through organized research, semi-organized interviews with guardians and parental figures, and clinical assessments led by dental experts. The research utilized the Dental trauma Guide and the Changed Ellis Grouping for evaluating dental injuries. Quantitative data analysis was performed utilizing SPSS software, while qualitative data were broke down utilizing topical investigation to recognize normal topics and examples in management rehearses. Results: Independent t-tests, relationships, and various relapse examinations were led to test the hypothesis. Independent t-tests showed massive contrasts in the commonness and the board of dental trauma in light of the sort and seriousness of wounds (t = - 2.56, p = .01 for breaks; t = - 3.12, p = .002 for luxations). Correlation analysis uncovered a critical positive connection between brief mediation and successful results (r = 0.35, p < .01) and huge negative connections between deferred treatment and inconveniences (r = - 0.29, p < .01). Regression analysis demonstrated that quick attention and suitable follow-up were critical indicators of positive results (β = .322, t = 4.45, p < .001, R² = .104 for guaranteed care; β = .298, t = 3.78, p < .001, R² = .089 for follow-up). Conclusion: The research planned to survey the management techniques for dental trauma in children. The discoveries uncovered that ideal and proper management is related with better recuperation and less inconvenience. The research reasons that quick mediation and exhaustive subsequent consideration are vital in the management of dental trauma in children, featuring the significance of thorough dental consideration practices to guarantee ideal oral wellbeing results and in general prosperity. Keywords: Dental Trauma, Children, Management Strategies, Immediate Care, Follow-Up Care